SPACE PROSPECT IN THE FLEXIBLE ERA OF LATE CAPITALISM - Nihan Muş Özmen (Konya Technical University Faculty of Architecture and Design, 2020)
This study is mainly influenced by the idea of Manfredo Tafuri that architecture cannot fulfil its ideological task since it started serving capitalism and there are no more utopias. In his book Architecture and Utopia: Design and Capitalist Development, Tafuri discusses the socio-philosophical tangle in which architects have been struggling since the 18th century. According to Tafuri, the drama of today's architecture is the obligation to return to pure architecture, a matter of form without utopia, supreme uselessness.